Rendimento de grãos de cultivares de soja em diferentes formas de semeadura e densidade de plantas - Fontana, Emanuel (2016)
Soybean (Glycine max (L.) Merrill) is the leading culture of Brazilian agriculture. With today's global economy, there is greater demand of increased grain yield by adopting appropriate management practices, in which is detached the plant arrangement. These practices aim to maximize the use of environmental factors, not raise production costs and provide greater compet itiveness. In this sense, it is aimed to evaluate the growth characteristics and yield of soybean grain depending on the form of seeding and density of the plants. Two experiments were conducted in the growing season of 2013/2014 and 2014/15, with BMX Ativa RR cultivars (determined growth) and BMX Alvo RR (indeterminate growth) seeded at a spacing of 45 cm between rows and cross-seeding in five plant density (180, 240, 300, 360, 420,000 plants ha-1). It was evaluated the plant height, leaf area index, percentage of soil coverage, the first pod height, number of pods per square meter, number of grains per pod. Weight of one thousand of grains and grain yield. The overall result obtained showed higher plant height in the V6 stage in cross -seeding in two years. In Year 1, cultivate BMX Ativa had the highest plant height in V6 and R2 stages. The increase in plant density increases the height of plants in Year 1 in the V6 stage and two years at R2 stage. The leaf area index was higher in the cross-seeding in both years. Cultivar BMX Alvo RR showed higher IAF regarding BMX Ativa RR, and the increasing of plant density increased IAF. The percentage of ground cover index was higher in the cross-seeding, and as a result of increased plant density. The height of insertion of the first pod was smaller in crossseeding, cultivating BMX Alvo RR had a greater insertion of the first pod in relation to BMX Ativa RR and increasing plant density raised the height of insertion of the first pod. The number of pod per square meter, it was higher in Year 1 , it was higher in cross-seeding, and in Year 2 was higher in the planting spacing of 45 cm. Cultivar BMX Ativa RR showed higher number of pods per square meter and the increased density increased the number of pods per square meter. The number of seeds per pod was higher in cross-seeding and growth of density increased the number of seeds per pod. The weight of a thousand grains in Year 1 was higher in cross-seeding, and in Year 2 was higher in the planting spacing of 45 cm. In both years the PMG was higher in growing BMX Alvo RR. The grain yield was higher in the cross-seeding, and growth of plant density increased grain yield.